PENDIDIKAN ISLAM DALAM PENGEMBANGAN EKONOMI ISLAM - Fadli, Adi (widya balina, 2022)
his article examines how the development of Islamic economics is based on the Book of Bintang Perniagaan Pada Kelebihan Perusahaan by TGH. M. Shaleh Hambali Bengkel with a thematic approach (Al-Qur'an and Hadith). Including three domains traced: How is the concept of Islamic education in the development of Islamic Economics, the interpretation of the Qur'an used and the sanad al-Hadith used. This article ultimately leads to the concept of Islamic education in Economic Development in TGH's M. Shaleh Hambali Bengkel's book; those are 1. Education as a Wasilah for Islamic Economic Development; 2. Using the Quran as a basis for proof agrees with Asbabun Nuzul. 3. Sanad al-Hadith in the book can be traced through several mu'tabarah books.